TECTONIC SUBDIVISION OF THE CHUKCHI AND EAST SIBERIAN SEAS - Mazarovich A.O.; Sokolov S.Yu. (My University, 2003)
A tentative tectonic subdivision for the Chukchi and East Siberian seas has been created based on the processing and analysis of new satellite altimetry and magnetic data and published materials that include information in electronic formats. The Chukchi Sea shelf is composed of correlatives of the Alaskan tectonic zones. The main Alaskan thrust does not stretch into Wrangel Island but is instead located in the region of the South Chukchi Sea Basin. Most part of the shelf is occupied by a zone of zero or slight deformation. The North Chukchi Sea Basin along with the Vilkitsky Trough and the region of maximum subsidence in the Colville Trough make a single entity, the Novosibirsk-Alaska Basin.
Keywords: TECTONIC SUBDIVISION; CHUKCHI AND EAST SIBERIAN SEAS; SATELLITE ALTIMETRY; MAGNETIC DATA